Case report: Potential role of immunotherapy in thymic malignancies: a unique case of a durable and complete response upon an immune checkpoint inhibitor - Luciano, Angelo; Pietroluongo, Erica; Ottaviano, Margaret; Grieco, Angela; Peddio, Annarita; De Placido, Pietro; Servetto, Alberto; Mascolo, Massimo; Varricchio, Silvia; Bianco, Roberto; Palmieri, Giovannella; Giuliano, Mario (Frontiers in Immunology, 2024)
Thymic epithelial tumors are rare malignancies with an incidence of 1.7 cases per million people per year. They pose significant management challenges due to their association with autoimmune disorders.In this case report, we present the 21-year history of a patient diagnosed with advanced B2/B3 thymoma and Good's syndrome. The patient achieved a complete and durable response after receiving only two cycles of the immune checkpoint inhibitor Nivolumab. However, this positive outcome was accompanied by the development of severe immune-related myocarditis complicated by reactivation of cytomegalovirus. Moreover, the patient developed a highly uncommon subdiaphragmatic pararectal dissemination of the thymic tumor, which is a condition rarely described in the literature.Despite the success in achieving complete and durable response with immune checkpoint inhibitors, the emergence of immune-related adverse events highlights the potential challenges associated with these treatments, emphasizing the need for careful monitoring and a comprehensive understanding of the intricate interplay between cancer, immune system dysregulations and immunotherapy.